1985
DOI: 10.1128/mcb.5.6.1385
|View full text |Cite
|
Sign up to set email alerts
|

Mutant strain of Chinese hamster ovary cells with no detectable ornithine decarboxylase activity.

Abstract: We previously described an arginase-deficient, polyamine-dependent Chinese hamster ovary cell line which grows in serum-free medium. From this strain we isolated a new mutant strain that has no detectable catalytic ornithine decarboxylase activity. The mutant cells contain, however, immunoreactive ornithine decarboxylaselike protein roughly in the same quantity as the parent strain. The mutant and the parent cell line strains also contain similar amounts of ornithine decarboxylase-mRNA hybridizable to a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Unfortunately, the effect of DFMO has not been as effective in vivo, where the antiproliferative activity is substantially diminished. Two major mechanisms are considered to be responsible for this discrepancy: amplification of ornithine decarboxylase, resulting in resistance to DFMO, and upregulation of polyamine import from the extracellular compartment (40)(41)(42). Although other inhibitors are available that target different enzymes in the pathway {e.g., methylglyoxal bis(guanyl hydrazone), CGP 48664, S-(5Ј-deoxy-5Ј-adenosyl)-methylthioethyl-hydroxylamine, 1-aminooxy-3-aminopropane, and ([4-amino-2-butenyl]methylamino)-5Ј-deoxyadenosine}, the enhanced uptake of polyamines caused by decreased de novo synthesis remains a problem.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the effect of DFMO has not been as effective in vivo, where the antiproliferative activity is substantially diminished. Two major mechanisms are considered to be responsible for this discrepancy: amplification of ornithine decarboxylase, resulting in resistance to DFMO, and upregulation of polyamine import from the extracellular compartment (40)(41)(42). Although other inhibitors are available that target different enzymes in the pathway {e.g., methylglyoxal bis(guanyl hydrazone), CGP 48664, S-(5Ј-deoxy-5Ј-adenosyl)-methylthioethyl-hydroxylamine, 1-aminooxy-3-aminopropane, and ([4-amino-2-butenyl]methylamino)-5Ј-deoxyadenosine}, the enhanced uptake of polyamines caused by decreased de novo synthesis remains a problem.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been recognized that the activity of ornithine decarboxylase (ODC), the first enzyme in the polyaminebiosynthetic pathway that forms putrescine, is necessary for mammalian cell growth (Mamont et al, 1978;Pohjanpelto et al, 1981Pohjanpelto et al, , 1985Steglich and Scheffler, 1982). Many studies have now been carried out with inhibitors of this enzyme [reviewed by Pegg and McCann (1982), Danzin and Mamont (1987) and Pegg (1988)].…”
Section: Introductionmentioning
confidence: 98%
“…Subsequent studies by the Merrell group and others, using specific ODC inhibitors (9 -14) or genetic approaches (15,16) to manipulate levels of endogenous polyamines, confirmed that amines derived from ornithine are essential for mammalian cell viability, and high levels are necessary for optimal mammalian cell growth. Corroborative results, demonstrating the importance of the polyamines for viability and growth, were also obtained in nonmammalian systems.…”
Section: Early Rationale For the Development Of Inhibitors Of Polyamimentioning
confidence: 99%